Analysis of Human Serum and Whole Blood for Mineral Content by ICP-MS and ICP-OES: Development of a Mineralomics Method - Harrington, James M. (2014)
Minerals are inorganic compounds that are essential to the support of a variety of biological functions. Understanding the range and variability of the content of these minerals in biological samples can provide insight into the relationships between mineral content and the health of individuals. In particular, abnormal mineral content may serve as an indicator of illness. The development of robust, reliable analytical methods for the determination of the mineral content of biological samples is essential to developing biological models for understanding the relationship between minerals and illnesses. This manuscript describes a method for the analysis of the mineral content of small volumes of serum and whole blood samples from healthy individuals. Interday and intraday precision for the mineral content of the blood (250 μl) and serum (250 μl) samples was measured for eight essential minerals, sodium (Na), calcium (Ca), magnesium (Mg), potassium (K), iron (Fe), zinc (Zn), copper (Cu), and selenium (Se) by plasma spectrometric methods and ranged from 0.635 – 10.1% relative standard deviation (RSD) for serum and 0.348 – 5.98% for whole blood. A comparison of the determined ranges for ten serum samples and six whole blood samples provided good agreement with literature reference ranges. The results demonstrate that the digestion and analysis methods can be used to reliably measure the content of these minerals, and potentially to add other minerals.